THE ROLE AND PLACE OF MATHEMATICS IN THE SYSTEM OF SECONDARY VOCATIONAL EDUCATION - Detkova, Ana (Acta et Commentationes, Sciences of Education, 2019)
The article describes the main problems education of mathematics in the system of secondary professional education and the possible ways of solving them. Analysis this problems can become a basis of formation of mathematical apparatus, as an instrument for the development of the profession